Recent developments in the diagnosis of avian influenza - Okamatsu, Masatoshi; Hiono, Takahiro; Kida, Hiroshi; Sakoda, Yoshihiro (The veterinary journal (1997), 2016)
•The diagnosis of avian influenza is difficult due to diversity of hosts and viruses.•Recent developments in molecular techniques have accelerated rapid diagnosis.•Diagnostic techniques should be combined according to their advantages.•Genetic detections of the influenza A virus are rapid and sensitive laboratory tests.•Immunochromatography has been widely used in diagnostic laboratories. The diagnosis of influenza A virus infections in poultry or wild birds is difficult due to variations in the pathogenicity of the viruses in different avian hosts and also the antigenic and genetic diversity of the virus, particularly the recent H5 highly pathogenic avian influenza viruses. A classical standard laboratory technique is virus isolation prior to subtyping and pathotyping. This diagnostic technique is crucial for further virological analyses, particularly during an initial outbreak; however, delays in diagnosis have thwarted effective disease control in recent years. Recent developments in molecular biological techniques provide an accelerated diagnosis. Such technologies, which include real-time reverse transcriptase PCR, isothermal nucleic acid amplification, next-generation sequencing and immunochromatography, contribute to simpler and more rapid diagnosis. The advantages of each of these diagnostic techniques should be considered for effective control of avian influenza.